Building a RAFFT: Impact of a professional development program for women faculty and residents in emergency medicine. Issue 3 (23rd June 2022) - Li‐Sauerwine, Simiao; Bambach, Kimberly; McGrath, Jillian; Yee, Jennifer; Boulger, Creagh T.; Hunold, Katherine M.; Mitzman, Jennifer
Abstract: Background: Women comprise 28% of faculty in academic departments of emergency medicine (EM) and 11% of academic chairs. Professional development programs for women are key to career success and to prevent pipeline attrition. Within emergency medicine, there is a paucity of outcomes‐level data for such programs. Objectives: We aim to measure the impact of a novel structured professional development curriculum and mentorship group (Resident and Faculty Female Tribe, or RAFFT) within an academic department of EM. Methods: This prospective single‐center curriculum implementation and evaluation was conducted in the academic year 2020–2021. A planning group identified potential curricular topics using an iterative Delphi process. We developed a 10‐session longitudinal curriculum; a postcurriculum survey was conducted to assess the perceived benefit of the program in four domains. Results: A total of 76% of 51 eligible women attended at least one session; for this project we analyzed the 24 participants (47%) who attended at least one session and completed both the pre‐ and the postsurvey. The majority of participants reported a positive benefit, which aligned with their expectations in the following areas: professional development (79.2%), job satisfaction (83.3%), professional well‐being (70.8%), and personal well‐being (79.2%). Resident physicians more often reported less benefit than expected compared to fellow/faculty physicians. Median perceived impact on career choice and trajectory was positive for all respondents. Conclusions: Success of this professional development program was measured through a perceived benefit aligning with participant expectations, a positive impact on career choice and career trajectory for participants in each career stage, and a high level of engagement in this voluntary program. Recommendations for the successful implementation of professional development programs include early engagement of stakeholders, the application of data from a program‐specific needs assessment, early dissemination of session dates to allow for protected time off, and structured discussions with appropriate identification of presession resources.